PAK-CHINA ECONOMIC RELATIONS IN THE PERSPECTIVE OF CPEC AND ITS IMPLICATION FOR THE REGION - Altaf Hussain; Jansher Khan; Shahab Uddin (International Journal of Contemporary Issues in Social Sciences, 2024)
The China-Pakistan Economic Corridor (CPEC) is a flagship project of BRI, aimed at connecting China’s Kashgar City with Pakistan’s Gwadar Port. China’s Belt and Road Initiative (BRI) focuses on connecting the CPEC with the entire region, including Iran, Afghanistan, India, Nepal, Bangladesh and Central Asian Republics. The CPEC aims to boost the economy and promote regional integration, increasing trade and economic activity within the region. This study examines Pak-China economic relations in the context of CPEC and its implications for the region, using both descriptive and historical approaches. While employing a qualitative method is preferred in which the secondary sources of data has been used. The study concludes that the CPEC’s link with regional countries is crucial and will support the local economy.